2006
DOI: 10.2337/db06-0519
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Induced Extracellular Matrix Protein Expression Is Mediated by Transcription Coactivator p300

Abstract: Increased fibronectin expression is a key feature of diabetic angiopathy. We have previously shown that nuclear factor-B (NF-B) mediates fibronectin expression in endothelial cells and in organs affected by diabetes complications. p300, a transcription coactivator, may regulate NF-B activity via poly(ADP-ribose) polymerase (PARP) activation. Hence, we examined the role of p300 in fibronectin expression in diabetes. High glucose induced fibronectin expression in the endothelial cells, which was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
119
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 33 publications
17
119
0
1
Order By: Relevance
“…Of note, ET-1 has been demonstrated to be of significance in EndMT in the diabetic heart (9). We also have demonstrated that p300 is upregulated in the cardiac tissues of diabetic animals (10). p300-Mediated histone acetylation is a key mechanism in regulating gene transcription.…”
mentioning
confidence: 80%
“…Of note, ET-1 has been demonstrated to be of significance in EndMT in the diabetic heart (9). We also have demonstrated that p300 is upregulated in the cardiac tissues of diabetic animals (10). p300-Mediated histone acetylation is a key mechanism in regulating gene transcription.…”
mentioning
confidence: 80%
“…7). The transcriptional co-activator p300 also functions as a HAT for H3/H4 and has been shown to interact with other E-box-binding proteins (21, 24 -27) and to be involved in the regulation of glucose-regulated genes (21)(22)(23). Its interaction with ChREBP may therefore not only explain how ChREBP induces H4 acetylation and recruitment of Pol II to the txnip promoter but may also be key for the molecular understanding of the regulation of other ChREBP target genes and their potential chromatin modification and transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional co-activator and histone acetyltransferase (HAT) p300 has been shown to regulate the expression of other glucose-responsive genes, such as insulin and fibronectin (21)(22)(23), and to physically interact with other E-box-binding basic helix-loop-helix proteins, such as NeuroD (21), USF2 (24), MyoD (25), SREBP (26), and Myc (27). Moreover, p300 is one of the major HATs (in addition to HAT1 and TIP 60) that acetylate H4.…”
Section: The Txnip Promoter Contains a Putative Chrebp Binding Site-mentioning
confidence: 99%
“…Remarkably, histone acetylation at inflammatory gene promoters in a CREB/ p300 (HAT)-dependent manner can be affected by oxidized lipids so that gene expression drives increased (36). In addition, PARP and NF-γB signaling was performed by p300 pathways in diabetic retina, kidney and heart, and led to extracellular matrix (ECM) components augmentation resulting in DVC (37)(38)(39)(40)(41)(42). Research in epigenetic showed that HDACs play a crucial role in TGF-β1-mediated ECM generation and renal parenchymal fibrosis (43)(44)(45).…”
Section: Histone Modificationmentioning
confidence: 99%
“…Furthermore, blood pressure control and fluid reabsorption are associated to dynamic regulation of H3K79 methylation (52)(53)(54)(55)(56). In addition, risk of diabetic complications increased as H3K4me and recruitment of SET7/9 to the insulin promoter region are augmented (38,56). Hyperglycemic memory may implicate epigenetic modifications through a transient hyperglycemia (57,58).…”
Section: Histone Modificationmentioning
confidence: 99%